2006
DOI: 10.1109/mcg.2006.109
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Design of Direct-Touch Tabletops

Abstract: Tables provide a large and natural interface for supporting direct manipulation of visual content for human-to-human interactions. Such surfaces also support collaboration, coordination, and parallel problem solving. However, the direct-touch table metaphor also presents considerable challenges, including the need for input methods that transcend traditional mouse-and keyboardbased designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 14 publications
0
56
0
3
Order By: Relevance
“…To support the collaborative aspect of bug triaging, we moved away from traditional point-and-click interfaces and developed our application for a multi-touch tabletop, since studies have shown that these inherently support collaboration [11]. By switching to a multi-touch environment, the application, as well as the bug triaging process itself, become more interactive and therefore might foster the collaboration between its users.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To support the collaborative aspect of bug triaging, we moved away from traditional point-and-click interfaces and developed our application for a multi-touch tabletop, since studies have shown that these inherently support collaboration [11]. By switching to a multi-touch environment, the application, as well as the bug triaging process itself, become more interactive and therefore might foster the collaboration between its users.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Furthermore, to better support the communication and collaboration between developers, we explicitly designed our approach for interactive tabletops that allow multiple people to interact with the information simultaneously. Other research has already shown that interactive tabletops inherently support collaboration (e.g., [11]). …”
Section: Collaborative Bug Triagingmentioning
confidence: 99%
“…2. Interacción con objetos tangibles: proveer al estudiante de instrumentos que sean más naturales de utilizar ya que conducen a una menor carga cognitiva (Shen, 2006). 3.…”
Section: Trabajos Relacionadosunclassified
“…Command menus and tool palettes present challenges with respect to orientation, reachability, and clutter [35] which can addressed by moving such interface elements from the surface to a mobile.…”
Section: Cross-device Interaction Techniquesmentioning
confidence: 99%